Effects of supply chain management practices on customer satisfaction: evidence from pharmaceutical industry of Bangladesh - Haque, Mahbubul; Islam, Rafikul (Universal Publishers, Boca Raton, Florida, 2013)

(untitled)
Purpose: Supply Chain Management (SCM) practices can significantly impact one aspect of organizational outcomes, i.e., customer satisfaction of drug manufacturers in the pharmaceutical industry. This study, therefore, seeks to find out the influencing dimensions of SCM practices and examine empirically the conceptual framework of proposed relationships between these dimensions and customer satisfaction. Design/methodology/approach: A quantitative survey was carried out among the managers and executives of various drug manufacturers in the pharmaceutical industry of Bangladesh. A total of 160 respondents with a response rate of 48% participated in the study. Factor analysis and structural equation modeling using AMOS version 16.0 were employed as statistical techniques to carry out the objectives of the study. Research limitations: The study is performed only in a particular industry and with a questionnaire survey. Future studies could extend the findings covering other industries as well as conducting a qualitative exploration of the pertinent dimensions of SCM practices. Practical implications: The findings of the study have a significant bearing for the managers working in pharmaceutical industry. The dimensions and their constituent items offer a significant insight into the current SCM practices impacting customer satisfaction and room for potential improvements in this regard.